Students Voices: A Qualitative Study On Teachers’ Written Feedback Among Fourth Year University Students - Bahri, Syamsul (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2019)
The objectives of this study is to find student’s voices on teachers’ written feedback. The qualitative study investigates the student’s voices on teachers’ written feedback of their essays and comments that benefit students’ future improvement as writers. It explores sixty-one English Department students’ opinions on the written feedback of their writing teachers at Ar-Raniry State University of Islamic Studies, Banda Aceh, Indonesia.  The findings indicate that writing teachers provide various kinds of feedback on students’ essays and they valued positive teachers’ feedback on all aspects of writing such as grammar, mechanics, content and organisation. Teachers’ negative comments were also considered useful for students’ learning because they can help students to improve their critical thinking and writing skills. In addition, for student future improvement, teachers’ feedbacks do contribute to learning and that teachers’ feedback on grammar and organisation are more preferable than those on content and mechanics. It is suggested that feedback which highlights strengths and weaknesses of students’ work can facilitate students to learn and make better future learning.